2015
DOI: 10.1371/journal.pone.0134114
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Analysis of Tumor Necrosis Factor α-Induced Protein 8-Like-1 (TIPE1) Protein

Abstract: Tumor necrosis factor α-induced protein 8 (TNFAIP8)-like protein 1 (TIPE1) was a member of TNFAIP8 family. Previous studies have shown that TIPE1 could induce apoptosis in hepatocellular carcinoma. In this study, we attempted to predict its potential structure. Bioinformatic analysis of TIPE1 was performed to predict its potential structure using the bioinfomatic web services or softwares. The results showed that the amino acid sequences of TIPE1 were well conserved in mammals. No signal peptide and no transme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…As a negative regulator of immunity and inflammation, TIPE2 expression levels are downregulated in most types of cancer tissues compared with those in adjacent normal tissues ( 5 , 20 23 ). However, a previous study has reported higher levels of TIPE2 protein in tissues from patients with CRC compared with those in healthy human colon tissues collected by colonoscopy ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a negative regulator of immunity and inflammation, TIPE2 expression levels are downregulated in most types of cancer tissues compared with those in adjacent normal tissues ( 5 , 20 23 ). However, a previous study has reported higher levels of TIPE2 protein in tissues from patients with CRC compared with those in healthy human colon tissues collected by colonoscopy ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, high expression levels of TIPE1 are detected in most human carcinoma cell lines, including cervical and ovarian cancer cell lines ( 5 , 19 ). Different posttranslational modifications of TIPE1 have also been predicted to exist ( 12 , 20 ). TIPE1 has two transcript variants, both of which encode the same protein ( , accessed on 23 December 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In a Parkinson’s disease model, TIPE1 binds to FBXW5, increasing autophagy through activation of TSC2 [ 20 ]. Due to the three-dimensional structure of TIPE1 protein, TIPE1 was predicted to interact with FBXW5, caspase8 and so on [ 21 ]. In our study, we found TIEP1 arrest NSCLC cancer cell cycle, inhibited apoptosis and metastasis (Figures 3 – 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…This family is comprised of four members, namely, TIPE or TNFAIP8 (tumor necrosis factor-α-induced protein 8), TIPE1 (TNFAIP8-like 1, or TNFAIP8L1), TIPE2 (TNFAIP8-like 2 or TNFAIP8L2), and TIPE3 (TNFAIP8-like 3 or TNFAIP8L3) [ 1 ]. Despite the fact that all the four proteins of this family share a significant sequence homology (~54% sequence identity), they are involved in the regulation of different cellular activities [ 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, TIPE1 was speculated to be associated with cardiac decompensation linked with diabetes and to interact with FBXW5 and caspase-8. Besides, different post-translational modifications were also predicted to exist in the case of TIPE1 [ 2 , 16 ].…”
Section: Introductionmentioning
confidence: 99%